Effects of spray-dried blood cells in lactation diets on sow and litter performance - E Weaver; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
High producing sows were used to evaluate the effect of spray-dried blood cells as a dietary protein source on lactation performance and subsequent reproductive performance. No significant differences were observed between sows fed a corn-soybean cells-based diet or a diet containing 2.5% spray-dried blood cells for lactation performance or subsequent reproductive performance. Therefore, spray-dried blood cells can be used as a partial replacelnent for the protein source in lactation diets.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Spray-dried blood cells; Lactation; Reproduction